A Spectrum of Hematological Disorders in Children with Pancytopenia Based on Bone Marrow Examination in a Tertiary Care Hospital - Zeeshan, Raana; Irshad, Bilal; Aslam, Muhammad A; Khan, Muhammad T; Bhatti, Hamza Waqar; Chaudhary, Noman A (Curēus (Palo Alto, CA), 2019)
IntroductionPancytopenia is a common presentation in the pediatric population. It is a manifestation of various diseases, and its etiology can be explained on the basis of bone marrow examination. The study aims to determine the etiological factors leading to pancytopenia via bone marrow examination in pediatric patients presenting in our hospital.Materials and methodsThis retrospective cross-sectional study was conducted in the Department of Pathology at a public sector tertiary care hospital. Data were recorded by convenience sampling from the patients’ database from January 2015 to April 2018. Patients aged 2 months to 15 years who had pancytopenia on peripheral blood smear and were admitted for bone marrow examination were included in the study. Patients who were beyond these age limits, diagnosed cases of aplastic anemia and leukemia, and those with a recent history of blood transfusion were excluded from the study. The analysis was done via the Statistical Package for Social Sciences (SPSS) v.23.0 (IBM SPSS Statistics, Armonk, NY, USA), and descriptive statistics were applied.ResultsOf 115 cases, 58 (50.4%) were males and 57 (49.6%) were females. Megaloblastic anemia was present in 32 (27.8%) patients, and it was the most common cause of pancytopenia. Non-malignant disorders were seen in 95 cases (82.6%) and malignant disorders were seen in 20 (17.4%) cases.ConclusionMegaloblastic anemia is the most common cause, and acute lymphoblastic leukemia is the most common malignant cause of pancytopenia in children. There was no significant gender predilection among causes of pancytopenia.